The interregional disparity in the choice of health care utilization among elderly in India - Jhumki Kundu; Mrinmoy Pratim Bharadwaz; Sampurna Kundu; Dhananjay W. Bansod (Elsevier, 2022)
Background: The elderly population in India is expanding fast, which indicates a growing share of people with more specialized needs for health and support. One of the prominent issues is the choice of health care services among the elderly, leading to its impact on health expenditure. Under Andersen's Health Behavioral Model, this study attempts to examine the nature of interregional disparity in the choice of health care services, along with investigating the choice-making in hospitalization services between private and public sources among the elderly. Besides, this study also comprises the regional dynamics of geriatric health care utilization. Methods: The current study uses data from the NSS, 75th round. The difference between choice in healthcare utilization and inpatient out-of-pocket (OOP) expenditure showed using the t-test and Z-test. The study also uses binary logistic regression analysis to explore the association of predisposing, enabling, and need factors with health services utilization. Results: The results suggest that the utilization of public facilities for inpatient services was very low, except in eastern and north-eastern states. Caste, education, monthly per capita expenditure (MPCE), and need for surgery were the main factors explaining the choice of either public or private facilities. Conclusion: The findings of the study stresses the need to provide suitable health facilities for India's senior population in the hospital, which may help policymakers better understand their health care needs.